Non-target and suspected-target screening for potentially hazardous chemicals in food contact materials: investigation of paper straws. Issue 4 (2nd April 2020) - Rusko, Janis; Perkons, Ingus; Rasinger, Josef D.; Bartkevics, Vadims
ABSTRACT: A non-target screening strategy was developed for the safety evaluation of potentially hazardous chemicals in paper food contact materials (FCMs). A tentative list of suspect analytes was generated using publicly available FCM substance inventories, the presence of contaminants in paper straws was confirmed by high-resolution Orbitrap mass spectrometry. Data-independent and data-dependent MS and MS/MS results for candidate compounds were processed using a workflow including peak detection by deconvolution, blank subtraction, retention time alignment, formula assignment and fragmentation spectra search against spectral libraries followed by in silico generated spectra annotation. This workflow allowed for the identification of 74 suspect compounds, of which 40 were assigned a high confidence level of detection. A tentative in silico toxicity evaluation for mutagenic and carcinogenic activities was carried out. Using quantitative structure–activity relationship (QSAR) models it was found that two of the detected compounds tested positive for mutagenicity and three for carcinogenicity. Graphical Abstract: